An Examination of Inmate Physical Assaults on Jail Correctional Staff: Exploring Inmate-Level and Jail-Level Conditions in the United States. Issue 11 (1st November 2016) - Williams, Cynthia-Lee; Porter, Jeremy R.
ABSTRACT: The current study examines individual-level determinants of inmate-on correctional staff assaults, particularly the demographic characteristics of inmates, and the context of structural/environmental characteristics of specific jails. Findings from a series of negative binomial regression models indicate some significant relationships, with additional analyses highlighting the nonlinear nature of the relationship between racial representation and assaults. The findings give credence to both the "lone-wolf" and "gang mentality" perspectives, in that jails with an unbalanced racial composition have higher rates of inmate assaults on correctional staff when groups are both under- and over-represented as a proportion of the jail population.